Manajemen Pendidikan Pesantren Integratif: Telaah Pemikiran Hidayat Nur Wahid dan Implikasinya Terhadap Tata Kelola Pesantren Pasca Undang-Undang Nomor 18 Tahun 2019 - Sofwan Manaf (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2026)
This study explores Hidayat Nur Wahid’s concept of integrative pesantren education and its implications for pesantren governance in Indonesia following the enactment of Law Number 18 of 2019 on Pesantren. Integrative pesantren is conceptualized as an educational model that systematically integrates classical Islamic scholarship with modern scientific knowledge within a unified institutional framework. The study aims to analyze this concept from an educational management perspective, examine its implications for governance, leadership, curriculum, and quality management, and formulate strategic recommendations for strengthening pesantren management. A qualitative library research approach was employed using content analysis of Hidayat Nur Wahid’s writings, the Pesantren Law, and relevant scholarly literature. Data were analyzed through the interactive model of Miles, Huberman, and Saldana, comprising data condensation, data display, and conclusion drawing. The findings demonstrate that integrative pesantren management is founded on four interrelated dimensions: curriculum integration, methodological integration, epistemological integration, and institutional integration. Furthermore, the implementation of the Pesantren Law requires adaptive governance that accommodates diverse pesantren typologies while addressing key managerial challenges, including transformational leadership, curriculum innovation, quality assurance, and financial governance. The study concludes that strengthening managerial capacity, developing context-sensitive quality standards, and enhancing institutional support are essential strategies for positioning integrative pesantren as a catalyst for educational transformation and sustainable national development toward Indonesia Emas 2045.